Chemical Properties, Total Phenolic Content, Total Anthocyanin, and Antioxidant Activity of Muntingia calabura Fermented Vinegar Macerate with Cannabis sativa and Mitragyna speciosa - Boonsupa, Wilawan; Chinakool, Supattra; Boonwiset, Chananchida; Kongnarong, Ornuma; Pimkhwan, Kanokwan (วารสารวิทยาศาสตร์ วิศวกรรมศาสตร์ และเทคโนโลยี มหาวิทยาลัยราชภัฏมหาสารคาม, 2023)
Muntingia calabura is a fruit found mainly in northeast of Thailand. The fruit is sweet and red when ripe. Processing into vinegar will encourage more utilization of the fruit. This objective of the study is vinegar production from Muntingia calabura wines, chemical properties total phenolic content, total anthocyanin, and antioxidant activity of fermented vinegar from Muntingia calabura that is macerated with 2 types of herbs: Cannabis sativa and Mitragyna speciosa. The first step made Muntingia calabura wine by using Saccharomyces cerevisiae (0.75% v/v of Muntingia calabura juice content) to produce alcohol. The second step made vinegar by inoculating Acetobacter pasteurianus 10 %(v/v) into Muntingia calabura wines which were adjusted alcohol content to 5.38 %(v/v), fermented at room temperature for 15 days. The results show that on the 5th day of alcoholic fermentation, the alcohol content was 6.45 %(v/v) and vinegar had acetic acid at 4.00 %(v/v). After that bring the herb (Cannabis sativa and Mitragyna speciosa) macerated in Muntingia calabura vinegar for 3 days. The highest antioxidant activity of Muntingia calabura vinegar macerated with Cannabis sativa was found to be 24.75 mg/mL. The highest total phenolic content and total anthocyanin of Muntingia calabura vinegar macerated with Mitragyna speciosa were 4.32 g/L and 50.94 mg/L, respectively. From this research, Muntingia calabura could be processed to make new, healthy products and further lead to income generation for people.